Parotidectomy outcomes, diagnosis and complications on pediatric patients; Twelve years of experiences in a tertiary care center - Kuşcu, Oğuz; Kayahan, Bahar; Önay, Övsen; Günaydın, Rıza Önder; Akyol, Mehmet Umut (The Turkish Journal of Pediatrics, 2016)
The aim of this study is to evaluate parotid masses management in pediatric population. From June 2002 to December 2014, 13 patients under the age of 18 with parotid tumors were treated via surgery at Hacettepe University Department of Otorhinolaryngology. Information on patients’ demographics, clinical and histopathologic tumor characteristics and treatment modalities with results was obtained from medical records, retrospectively. The age was ranging between 8-17 years. Ten (76.9%) patients had benign tumors and 8 (61.5%) of them were pleomorphic adenoma. One case had chronic sialadenitis with sialolithiasis and one patient had fluoride follicular hyperplasia. Three patients had malignant tumors; two of them were adenoid cystic carcinoma and one case of malignant melanoma metastasis. Twelve cases had undergone partial parotidectomy. Only one total parotidectomy was performed which was the patient with malignant melanoma. None of the patients had major complications or facial nerve palsy. During the 3 years follow up period, recurrence or Frey syndrome had not been detected but the case with malignant melanoma had distant metastasis during the follow up time. Although pediatric parotid masses are unusual, they can represent a variety of pathological diagnoses, including malignancy. Parotidectomy remains the mainstay of treatment and surgical experience is needed for low complication rates especially in children.